Komunikasi lelucon Tok Nan: Denotasi dan konotasi sematik yang signifikan - Mary Fatimah, Subet; Nurul Jannah, Roslan (2017)
Humors if used wisely in speeches will attract the attention of audiences. The late Datuk Patinggi Tan Sri Datuk Amar Hj.Adenan Hj Satem, jovially nicknamed as Tok Nan, the 5th Chief Minister of Sarawak used humors vastly and frequently in his speeches. His speeches were fun to listen at and thus often invited laughters. This research is done to identify humors in his speeches, analyzing the implicit meanings and put forward the reasons behind the usage. Fifteen Tok Nan's speeches were perused, analysed and transcribed. Words and utterances that are found to having elements of jokes are identified and randomly selected. The analyses were done by applying the denotation and connotation concepts meanings’ analyses in semantics. The study found that the elements of jokes used were a combination of several languages or dialects. This study also found that his speeches had specific meanings conveyed in jest. Proven as well were the funny words he used existed and are synonymous to that of a multiracial society in Sarawak which are collectively shared and understood. His jokes were well received because these humors indirectly entertained audiences, and thus conveyed and received without prejudice.